The 3GPP proposal for IMT-2000. - Chaudhury, P. (IEEE Communications magazine)
Market expectations for third-generation mobile radio systems (IMT-2000) show an increasing demand for a wide range of services from voice to low, high, and advanced data rate services to support mobile multimedia. This leads to technical requirements for IMT-2000 which are currently being standardized worldwide. Circuit- and packet-oriented services will be supported. These systems will operate in all radio environments to provide service to anyone, anytime, anywhere. The ITU has identified spectrum for the allocation of IMT-2000. However, these frequency bands are currently not available worldwide. In different regions research activities on IMT-2000 have been initiated to support the international consensus building process and standardization activities. Based on these activities system proposals have been submitted to ITU TG 8/1. In particular, the newly formed Third Generation Partnership Projects 3GPP and 3GPP2 have the objective of harmonizing similar proposals and defining detailed standards. Proposals from Europe, Japan, Korea, and the United States are very similar. The evolution and migration of second-generation systems to the third generation takes into account the deployed investment to save today's investment where useful and necessary. This article focuses on market and technical requirements and, in particular, the technical approach of 3GPP based on the big footprint of the GSM system